Circ_0078607 inhibits the progression of ovarian cancer via regulating the miR-32-5p/SIK1 network - Yangqiu Jin; Hui Wang (BMC, 2022)
Highlights 1. Circ_0078607 acts as a sponge of miR-32-5p. 2. MiR-32-5p targets SIK1.